The center of the circle is (h,k) = (-2,-3)
The radius of the circle is r = 2
The standard form of equation of the circle is
![{(x + 2)}^{2} + {(y + 3)}^{2} = 4](https://tex.z-dn.net/?f=%7B%28x%20%2B%202%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20%2B%203%29%7D%5E%7B2%7D%20%20%3D%204)
<h3>How to find the center, radius and standrad form of the circle?</h3>
The general form of equation of the circle is
![{(x - h)}^{2} + {(y - k)}^{2} = {r}^{2}](https://tex.z-dn.net/?f=%20%7B%28x%20-%20h%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%20k%29%7D%5E%7B2%7D%20%20%3D%20%20%7Br%7D%5E%7B2%7D%20)
Here, (h,k) means centre of the circle.
r means radius of the circle.
given that coordinate points of centre of circle is (-2,-3).
Hence the (h,k) = (-2,-3)
<h3>How to find the radius of the circle?</h3>
Now to find the radius of the circle
The distance from a circle's centre to its circumference is its radius.
The distance from a circle's centre (-2,-3) to its circumference (0,-3) is its radius.
using the formula, distance between the two points to obtain radius.
![d = \sqrt{(x1 - x2) {}^{2} + {(y1 - y2)}^{2} } \\ r = \sqrt{ {( - 2 - 0)}^{2} + {( - 3 - ( - 3))}^{2} } \\ r = \sqrt{ {( - 2)}^{2} + {( - 3 + 3)}^{2} } \\ r = \sqrt{ {4}^{2} + 0 } \\ r = \sqrt{4} \\ r = 2](https://tex.z-dn.net/?f=d%20%3D%20%20%5Csqrt%7B%28x1%20-%20x2%29%20%7B%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y1%20-%20y2%29%7D%5E%7B2%7D%20%7D%20%20%5C%5C%20r%20%3D%20%20%5Csqrt%7B%20%7B%28%20-%202%20-%200%29%7D%5E%7B2%7D%20%2B%20%20%7B%28%20-%203%20-%20%28%20-%203%29%29%7D%5E%7B2%7D%20%20%7D%20%20%5C%5C%20r%20%3D%20%20%5Csqrt%7B%20%7B%28%20-%202%29%7D%5E%7B2%7D%20%2B%20%20%7B%28%20-%203%20%2B%203%29%7D%5E%7B2%7D%20%20%7D%20%20%5C%5C%20r%20%3D%20%20%5Csqrt%7B%20%7B4%7D%5E%7B2%7D%20%2B%200%20%7D%20%20%5C%5C%20r%20%3D%20%20%5Csqrt%7B4%7D%20%20%5C%5C%20r%20%3D%202)
<h3>How to find the standard form of equation of the circle?</h3>
(h,k) = (-2,-3)
r = 2
subtitue the (h,k) and r values to get the standard form of equation of the circle.
![(x - h) {}^{2} + {(y - k)}^{2} = {r}^{2}](https://tex.z-dn.net/?f=%28x%20-%20h%29%20%7B%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%20k%29%7D%5E%7B2%7D%20%20%3D%20%20%7Br%7D%5E%7B2%7D%20)
![{(x - ( - 2))}^{2} + {(y - ( - 3))}^{2} = {r}^{2}](https://tex.z-dn.net/?f=%20%7B%28x%20-%20%28%20-%202%29%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%20%28%20-%203%29%29%7D%5E%7B2%7D%20%3D%20%20%7Br%7D%5E%7B2%7D%20%20)
![{(x + 2)}^{2} + {(y + 3)}^{2} = 4](https://tex.z-dn.net/?f=%20%7B%28x%20%2B%202%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20%2B%203%29%7D%5E%7B2%7D%20%20%3D%204)
Learn more about circle, refer:
brainly.com/question/24810873
#SPJ9